Influence of age on small incision lenticule extraction outcomes. Issue 3 (18th November 2020) - Primavera, Laura; Canto-Cerdan, Mario; Alio, Jorge L; Alio del Barrio, Jorge L
Abstract : Purpose: To evaluate the influence of patient's age at the time of surgery on small incision lenticule extraction (SMILE) refractive outcomes. Methods: This is a retrospective, consecutive, comparative study. We compared the refractive outcomes after myopic SMILE from two groups of patients divided by age (patients ≤35 and ≥40 years old). All eyes were evaluated preoperatively and at 1 and 6 months postoperatively. Main outcome measures were differences on efficacy, safety, predictability and astigmatic changes by vector analysis with ASSORT software between both study groups. Results: 102 matched eyes of 53 patients were included. Preoperatively, we evidenced no differences in the mean SE or astigmatism between groups. However, 6 months postoperatively we observed a significantly worse mean astigmatism (p=0.019), while not regarding SE, in the older population, with a trend towards undercorrection of the refractive cylinder in the ≥40 group. We also observed a statistically significant difference in the efficacy (0.86–1 month and 0.97–6 months in ≥40group vs 0.97–1 month and 1.07–6 months in the ≤35 group; p=0.003) and safety indexes (0.93–1 month and 1.04–6 months in ≥40 group vs 1.0–1 month and 1.11–6 months in the ≤35 group; p=0.008) at 6 months among groups. Conclusions: Post-SMILE refractive outcomes in those patients over 40 years of age, although acceptable, are not as good as those obtained in younger patients, showing a significantly lower efficacy and safety indexes, and poorer astigmatic outcomes, with a tendency towards undercorrection. We hypothetise that the increased corneal stroma stiffness in the aged group modifies the post-SMILE corneal stroma remodelling capacity, thus affecting the SMILE refractive and visual response.